Formula to use

$r^{th} \text{ term} = ({^nC_m})(a^{n - m})(b^m)$

For (*x* - 2/*x*)^{6}:

*a* = *x*

*b* = -2/*x*

*n* = 6

$r^{th} \text{ term} = ({^6C_m})(x^{6 - m})\left( -\dfrac{2}{x} \right)^m$

$r^{th} \text{ term} = ({^6C_m})(-2)^m (x^{6 - 2m})$

Let $({^6C_m})(-2)^m = K_j$

For the *r*^{th} term involving *K*_{1}*x*^{0}:

$6 - 2m = 0$
$m = 3$

$K_1 = ({^6C_3})(-2)^3 = -160$

For the *r*^{th} term involving *K*_{2}*x*^{2}:

$6 - 2m = 2$
$m = 2$

$K_2 = ({^6C_2})(-2)^2 = 60$

The constant term in the expansion of (2 + 3/*x*^{2})(*x* - 2/*x*)^{6} is:

$K = 2K_1 + 3 K_2 = 2(-160) + 3(60)$

$K = -140$ ← *answer*